Concept validation of separations for thorium-based radionuclide generator systems for medical application - Schacherl, Bianca; Maurer, Kiara; Schäfer, Martin; Remde, Yvonne; Geyer, Frank; Fried, Annika; Happel, Steffen Alexander; Benešová-Schäfer, Martina (Frontiers in Nuclear Engineering, 2024)
Targeted alpha therapy (TαT) represents an emerging and cutting-edge treatment option for patients dealing with highly challenging metastatic cancer diseases. Critically, the limited supply of alpha-particle-emitting radionuclides, so-called alpha in vivo nanogenerators, hampers wider utilization of TαT in clinical settings. This could effectively be circumvented by alternative production routes, including straightforward purification and reformulation strategies. Radionuclide generators offering great potential in simple and robust elution strategies can be provided that still adhere to high radioisotopic, radionuclidic, and radiochemical purity criteria. This study takes a first step towards novel separation strategies by providing additional sources of alpha in vivo nanogenerators for TαT through experiments with various metal surrogates. With different systems, 232Th/natBa was used as a radionuclide generator analogue to 227Th/223Ra, and 232Th/natBa/natLa was used as a triplet analogue to 229Th/225Ra/225Ac. Three selective resins (UTEVA, TEVA, DGA-N) were evaluated for the 232Th/natBa system. Two perturbations of the best-performing resin were further evaluated using a larger diameter column and 1 week of equilibration. For the 232Th/natBa/natLa separation system, a combined column with two selective resins (TK200, TK101) was employed and evaluated. The results thus obtained pave the way for alternative separation strategies in radioactive proof-of-concept validation in the near future.